Optimasi Kualitas Proses Bending untuk Mengurangi Deformasi Produk Menggunakan Metode Seven Tools dan PDCA di Industri Manufaktur - Sapto Yuli Nugroho; Muklisin Muklisin; Rudy Effendy Listyanto (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The pipe bending process in the manufacturing industry, particularly for air conditioner (AC) components, often faces quality problems in the form of flattening (ovalization) and wrinkle defects, which can reduce product functionality and strength. Initial data show that the defect rate reached 8.2%, exceeding the company’s target of ≤ 3%. This study aims to reduce these defects by applying the PDCA (Plan–Do–Check–Action) method supported by the Seven Quality Control Tools. Data were collected from 18,000 production units during the January–March period using check sheets and analyzed using histograms, Pareto diagrams, and fishbone diagrams to identify dominant defects and their root causes. Improvement actions included adjusting bending machine parameters, modifying the mandrel design, developing and implementing Work Instructions, adding measuring tools, applying lubrication, and providing operator training. The results show a significant reduction in nonconforming products from 691 units to 37 units, equivalent to 0.21% of total production, with the bending process operating in a stable and statistically controlled condition. Thus, the integration of PDCA and the Seven Quality Control Tools is proven to be effective in improving quality and production efficiency.